Bond performance between fibre-reinforced polymer bars and concrete under pull-out tests. (10th December 2019) - Wei, Wei; Liu, Feng; Xiong, Zhe; Lu, Zhongyu; Li, Lijuan
Highlights: Experimental study on bond performance between FRP bars and concrete. The diameter, type, and surface treatment of the FRP bars were considered. The failure mode and bond mechanism were summarized. Two new constitutive models for the whole bond stress–slip curve were proposed. A formula to estimate the practical anchorage length of FRP bars was proposed. Abstract: In this study, the bond performance between fibre-reinforced polymer (FRP) bars and concrete was investigated by means of forty-eight pull-out tests. The influences of the diameter, type, and surface treatment of the FRP bars were considered. Two failure modes, including the pull-out mode and concrete splitting, were observed. The bond mechanism, bond strength, and bond stress–slip curve were discussed. It was found that (1) The force transfer mechanism of FRP bars with sand coating was mainly controlled by friction, while that of bars with helical wrapping or screw thread was mainly controlled by mechanical interlocking. (2) Carbon fibre reinforced polymer (CFRP) bars and a helical wrapping or screw thread surface treatment could improve the bond strength. (3) The bond stress–slip curve of FRP bars with sand coating showed a very steep characteristic at the initial micro-slippage segment, while that of bars with helical wrapping or screw thread exhibited a periodic variation. Two new bond stress–slip constitutive models were proposed. Compared with the existing models, the proposed models had higher fitting accuracy and universal applicability for the whole bond stress–slip curve. Finite element (FE) models were established and verified. Based on the FE results, a formula to estimate the anchorage length of FRP bars was proposed.